2019
DOI: 10.3390/pharmaceutics11100512
|View full text |Cite
|
Sign up to set email alerts
|

Achillin Increases Chemosensitivity to Paclitaxel, Overcoming Resistance and Enhancing Apoptosis in Human Hepatocellular Carcinoma Cell Line Resistant to Paclitaxel (Hep3B/PTX)

Abstract: Multidrug resistance (MDR) has become a major obstacle in the treatment of cancer, and is associated with mechanisms such as increased drug outflow, reduction of apoptosis, and/or altered drug metabolism. These problems can be mitigated by the coadministration of agents known as chemosensitizers, as they can reverse resistance to anticancer drugs and eventually resensitize cancer cells. We explore the chemosensitizing effect of Achillin, a guaianolide-type sesquiterpene lactone isolated from the Mexican medici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 58 publications
(79 reference statements)
0
12
0
Order By: Relevance
“…Indeed, tumor cells are rapidly developing resistance to the majority of chemotherapeutic drugs resulting in tumor recurrence [67][68][69]. Interestingly, it has been shown that an abundance of natural substances may be used as adjuvants in cancer treatment regimens to reverse chemoresistance to chemotherapeutic drugs [70,71]. Several reports from ours and other laboratories have reported that tumor cells can acquire drug resistance by different mechanisms including mutation or overexpression of the drug target, inactivation of the drug or removal of the drug from the cell [16,72,73].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, tumor cells are rapidly developing resistance to the majority of chemotherapeutic drugs resulting in tumor recurrence [67][68][69]. Interestingly, it has been shown that an abundance of natural substances may be used as adjuvants in cancer treatment regimens to reverse chemoresistance to chemotherapeutic drugs [70,71]. Several reports from ours and other laboratories have reported that tumor cells can acquire drug resistance by different mechanisms including mutation or overexpression of the drug target, inactivation of the drug or removal of the drug from the cell [16,72,73].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the ligand efficiency (LE) [ 108 , 109 ] are also available as a parameter to evaluate the best diterpenes ( Table 4 and Table 5 ). The selected diterpenes for Aphis showed LE close to the insecticides while for Drosophila are similar or superior, suggesting this class of compounds as potential bioinsecticides.…”
Section: Resultsmentioning
confidence: 99%
“…This guaianolide-type sesquiterpene lactone has shown anti-inflammatory, antiallergic (IC 50 = 100 µM) and cytotoxic activity on SMMC-7721 cell lines [ 67 ]. Sanchez-Carranza et al [ 68 ] demonstrated that achillin enhances the cytotoxic effect of paclitaxel and the induction of G2/M phase cell cycle arrest and apoptosis when associating both drugs. This guainolide also reduced P-gp levels and increased the intracellular retention of doxorubicin in Hep3B/PTX cells.…”
Section: Biological Activitymentioning
confidence: 99%